Attitudes, knowledge and factors related to acceptance of influenza vaccine by pediatric healthcare workers - Livni, Gilat; Chodik, Gabriel; Yaari, Arnon; Tirosh, Naama; Ashkenazi, Shai (Journal of Pediatric Infectious Diseases, 2008)
The aim of this study was to identify factors that affect influenza vaccination in order to devise means to increase compliance. In February 2003, pediatricians attending a national medical conference and nurses in a university hospital in central Israel were asked to complete a questionnaire regarding occupational data, knowledge issues, and reasons for undergoing/not undergoing vaccination themselves. Physicians also reported their practice of recommending the vaccine. A total of 181 physicians and 217 nurses answered the questionnaires (compliance rate, 51%). Almost half (46.8%) had been vaccinated against influenza. There was a higher rate for physicians (60.8%) compared to nurses (35.2%), board-certified or board-eligible pediatricians (67.4%) compared to residents (44.7%), and for in-hospital physicians (67%) compared to community physicians (53%). Most frequent reason for vaccination was self-protection; and most frequent reason for non-vaccination was doubt about vaccine effectiveness. Physicians had better knowledge scores (68 ± 22 vs. 51 ± 23, p = 0.01). On multivariate regression analysis, the variables associated with getting influenza vaccine by physicians were knowledge concerning influenza vaccine (OR = 1.31), recommending the vaccine to patients (OR = 3.37), and specialist status (OR = 2.61). Increased knowledge concerning influenza vaccine is associated with increased vaccination rates among pediatric healthcare workers and their recommendation to vaccinate children.
Keywords: Influenza; vaccination; healthcare workers; pediatrics; compliance acceptance of influenza vaccine by pediatric healthcare workers